1992
DOI: 10.1152/ajpgi.1992.262.2.g319
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal and intracellular phases of fat absorption are impaired in essential fatty acid deficiency

Abstract: The structure and function of enterocyte membranes are particularly sensitive to the degree of fatty acid saturation. The objective of the present study was to assess intestinal fat transport in essential fatty acid (EFA)-deficient animal models. Both the digestive and absorptive phases leading to the formation and the secretion of triglyceride (TG)-rich lipoproteins were investigated. After an intraduodenal fat infusion, the percentage increase of plasma TG over fasting values was examined over a period of 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
2
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 0 publications
3
40
2
1
Order By: Relevance
“…The discrepancy regarding in vivo studies on lipoprotein clearance in EFAD rats (10,27) and our EFAD mouse model may be explained by species specificity. Previous studies have demonstrated that EFA deficiency has different effects on bile formation in rats and in mice (24,25,48).…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy regarding in vivo studies on lipoprotein clearance in EFAD rats (10,27) and our EFAD mouse model may be explained by species specificity. Previous studies have demonstrated that EFA deficiency has different effects on bile formation in rats and in mice (24,25,48).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as previously demonstrated for the oxidative status [15], pulmonary dysfunction seems to be more important than nutritional disorders in controlling the plasma FA profile, except for EFA deficiency, because the BMI affects linoleic acid positively and palmitoleic acid negatively. This point deserves careful investigation because diet is the only source of EFAs and because fat malabsorption is commonly thought to cause EFA deficiency, while EFA deficiency is also a known cause of fat malabsorption [33,34]. Furthermore, the transition from pulmonary inflammation to systemic inflammation should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In Vitro Experiments with BMS-200150 -ApoB synthesis was assessed in everted rat intestine, as described previously (44). Then, 300 Ci of […”
Section: Methodsmentioning
confidence: 99%